204k views
4 votes
Solve the following system by elimination,

Solve the following system by elimination,-example-1
User Aartiles
by
6.2k points

1 Answer

5 votes


2x - y = 9 \\ 3x + 4y = - 14 \\substitute \: that \: into \\ 2x = 9 + y \\ x = 4.5 + (y)/(2)
Substitute that into

3(4.5 + (y)/(2) ) + 4y = - 14 \\ 13.5 + (3y)/(2) + 4y = - 14 \\ 5.5y = - 27.5 \\ y = - 5
Substitute that into

2x - ( - 5) = 9 \\ 2x = 4 \\ x = 2

The answer is first option (2, -5)

Hope this helps. - M
User Saurabh Patil
by
5.8k points